Effect on nutritional status and biomarkers of inflammation and oxidation of an oral nutritional supplement (with or without probiotics) in malnourished hemodialysis patients. A multicenter randomized clinical trial “Renacare Trial” - Hevilla, Francisco; Padial, Marina; Blanca, María; Barril, Guillermina; Jiménez-Salcedo, Tamara; Ramirez-Ortiz, Mercedes; Nogueira, Ángel; Gentile, Adriana; García-Escobar, Eva; Romero-Zerbo, Silvana Y.; Olveira, Gabriel (Frontiers in Nutrition, 2023)
Background: Malnutrition in patients undergoing hemodialysis is frequent and associated with a reduction in muscular mass and strength, with an increment in biomarkers of inflammation and oxidation; Methods: randomized, multicenter, parallel-group trial in Malnourished Hemodialysis Patients with 3 groups (1: Control -C- individualized diet 2: Oral nutritional supplement -ONS- + placebo -SU-PL- and 3: ONS + probiotics -SU-PR); the trial was open regarding the intake of ONS or individualized diet recommendations, but double-blind for the intake of probiotics. We obtained, at baseline and after 3 and 6 months, anthropometric measurements, handgrip strength, bioelectrical impedance analysis (BIA), dietary records, and routine biochemical parameters. Inflammation and oxidation were determined using ELISA techniques (Versamax and ProcartaPlex multiplex Immunoassay). Results were analyzed by intention to treat; Results: 31 patients (11 corresponding to group C, 10 to SU-PL, and 10 to SU-PR) completed the six-months trial. The two groups that took supplements increased significantly their protein-calorie, fat (total and n-3), and fiber intake. Weight and fat-free mass (FFM) also increased significantly in the groups on supplements, both at 3 and 6 months, and dynamometry did so in the SU-PL group. At month 3, prealbumin and vitamin D were significantly increased in the SU-TOT (SU-PL+SU-PR) group. No changes were observed regarding levels of phosphorus and potassium in any of the groups. There were significant changes in some inflammation biomarkers in the groups on supplements during the intervention (BDNF, BMP2, MCP-1, IL1-beta, IL-10, IL-4, IL-8). The total antioxidant capacity (TAC) increased significantly in the supplemented patients, with no significant changes observed in isoprostanes. Conclusions: The specific ONS improved protein-calorie intake, nutritional status (mainly FFM) and some biomarkers of inflammation/oxidation. The addition of probiotics could have a synergistic effect with ONS in such biomarkers.